Anak Punk Jalanan di Jambi dalam Perspektif Hukum Pidana - Dedy Syaputra; Sartika Lia Apriana (Universitas Batanghari Jambi, 2020)
This phenomenon of street children in Jambi clearly proves a fact that the rights of children are not fulfilled by parents, society, or country. On the other hand, the variety and types of unofficial professions and occupational sectors in the city make city life more diverse from the angle of the types of jobs available. This is one of the factors that makes each individual including the children who attend school even interested in making a living, and the more unique case is in cities, the type of pecerajan for the age of adolescence is also widely available. This is why street children are more common in the city than in the village. If carefully observed, the point where street children gather is very dangerous. In addition to disturbing the order and comfort of others, it can also harm itself and provide opportunities for acts of violence. Even street children themselves have the potential to become criminous such as compressing their friends or other weaker individuals, petty theft, and the use of even trafficking drugs that are classified as substances that are harmful to health. To approach this issue, researchers used a qualitative paradigm from a criminal perspective. The findings of the data search results in the field are obtained as follows: (1) The causative factor of the number of street children in Jambi city is due to the unmet physical and psychic needs of the child, then, because of the personal desire of the street children themselves and environmental factors. (2) The impact of criminal problems that can lead to criminal acts from the appearance of street children are: the emergence of new social problems, disruption of city order, and threatening the safety and security of the citizens of the surrounding communities.